2023
DOI: 10.1158/1078-0432.ccr-23-0088
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Reduces the Inflammatory Response and Promotes Intestinal Mucosa-Associated Immunity in Lynch Syndrome

Nan Deng,
Laura Reyes-Uribe,
Johannes F. Fahrmann
et al.

Abstract: Purpose: Lynch Syndrome (LS) is a hereditary condition with a high lifetime risk of colorectal and endometrial cancers. Exercise is a non-pharmacological intervention to reduce cancer risk, though its impact on patients with LS has not been prospectively studied. Here, we evaluated the impact of a 12-month aerobic exercise cycling intervention in the biology of the immune system in LS carriers. Experimental Design: To address this, we enrolled 21 LS patients onto a non-randomized, sequential intervention assig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Exercise can enhance anti-tumor immunity. Natural killer and CD8 + cytotoxic T-cells expand, and immune suppressive myeloid-derived suppressor cells are reduced with exercise ( 17 - 19 ). Murine models have also shown that aerobic exercise and IL-15 activation will sensitize pancreatic tumor to IO treatment ( 20 ).…”
mentioning
confidence: 99%
“…Exercise can enhance anti-tumor immunity. Natural killer and CD8 + cytotoxic T-cells expand, and immune suppressive myeloid-derived suppressor cells are reduced with exercise ( 17 - 19 ). Murine models have also shown that aerobic exercise and IL-15 activation will sensitize pancreatic tumor to IO treatment ( 20 ).…”
mentioning
confidence: 99%